An 18-Year-Old Man with Idiopathic Non-cirrhotic Portal Hypertension - Irene Saveria; Syifa Mustika (Acta Medica Indonesiana)
Non-Cirrhotic Portal Hypertension (NCPH) is a rare cause of hematemesis and melena. Like in cirrhotic patient, hematemesis in NCPH patient was caused by rupture of esophageal varices. But unlike in cirrhotic patient, in NCPH there are no sign of liver failure, because liver physiology is still normal. We reported case of male patient with NCPH that had hematemesis because of rupture of esophageal varices.